Atrial fibrillation episode status and incidence of coronary slow flow: A propensity score-matched analysis - Gao, Ya-fang; Chen, Yan; Wang, Cheng-jian; Du, Ying; Ding, Ya-hui (Frontiers in Cardiovascular Medicine, 2023)
Background: Animal studies have demonstrated that induced atrial fibrillation (AF) leads to reduced coronary perfusion. However, whether AF episodes affect the incidence of coronary slow flow (CSF) in human samples has not been confirmed in studies. This study investigated the correlation between AF rhythm and CSF. Methods: We gathered patients with AF who underwent coronary angiography at our hospital between January 1, 2017, and April 30, 2022, and categorized them according to whether an AF attack occurred during the operation. The outcome indicators are the occurrence of CSF overall and in the three coronary arteries. The analysis was repeated after adjusting the baseline information by propensity score matching method (1:1 ratio). Results: 214 patients who met the inclusion and exclusion criteria were included (AF attack group: 100 patients, AF non-attack group: 114 patients). Before matching, the age, left atrial size, ejection fraction, heart rate, CSF incidence, and mean corrected TIMI frame counts were higher in patients with intraoperative AF attacks than in patients without attacks. After matching, baseline information was balanced mainly between the two groups of patients. The incidence of CSF (P=0.010, OR=2.327, 95% CI: 1.226-4.416) and heart rate (P=0.043, OR=1.024, 95% CI: 1.001-1.049) were significantly higher in the intraoperative AF attack group than in the no-attack group.